Growth and Liquidity on Firm Value : The Role of Mediating Profitability - Cahyani, Rahma Mauli; Khaerunnisa, Enis; Mahmudi, Bambang (Jurnal Riset Akuntansi Terpadu, 2024)
This study aims to determine the effect of Growth and liquidity on firm value with the role of profitability as a mediating variable in food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2014 - 2023. The data collection method used in this study is purposive sampling of food and beverage sub-sector companies listed on the Indonesia Stock Exchange for 2014 - 2023, with a selected sample of 11 companies. Data processing was done using the SPSS application, which used descriptive statistical data analysis techniques and inferential statistics. The results of this study indicate that: (1) Growth as proxied by asset growth has no significant effect on firm value. (2) Liquidity proxied by the current ratio has a significant negative effect on firm value. (3) Profitability proxied by return on assets can mediate the effect of Growth and liquidity on firm value.